2009
DOI: 10.3109/02699200903141271
|View full text |Cite
|
Sign up to set email alerts
|

A perceptual and electropalatographic study of /∫/ in young people with Down's syndrome

Abstract: Speech production in young people with Down's syndrome has been found to be variable and inconsistent. Errors tend to be more in the production of sounds that typically develop later, for example, fricatives and affricates, rather than stops and nasals. It has been suggested that inconsistency in production is a result of a motor speech deficit. Late acquired fricatives such as /s/ and /integral/ are complex articulations, which may require more precise motor programming and may therefore show highly inconsist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
(41 reference statements)
0
5
0
Order By: Relevance
“…As reviewed by McAuliffe and Ward (2006), several of these studies show differences in EPG patterns between speakers with dysarthria and neurologically-normal speakers, but the differences are often difficult (if not impossible) to interpret. For example, reports of apparently “atypical” palatal contact patterns associated with perception of a correct lingual consonant are fairly common (see cases reviewed by McAuliffe and Ward, 2006; and similar mismatches between EPG patterns and the perception of /Σ/ reported by Timmins et al (2009) for speakers with Down syndrome). McAuliffe, Ward, and Murdoch (2006) report the opposite effect for speakers with Parkinson disease, wherein apparently “normal” EPG patterns for lingual consonants are associated with consonants perceived as “imprecise”.…”
Section: 0 Candidate Measures For the Evaluation Of Dbs Effects On mentioning
confidence: 99%
See 1 more Smart Citation
“…As reviewed by McAuliffe and Ward (2006), several of these studies show differences in EPG patterns between speakers with dysarthria and neurologically-normal speakers, but the differences are often difficult (if not impossible) to interpret. For example, reports of apparently “atypical” palatal contact patterns associated with perception of a correct lingual consonant are fairly common (see cases reviewed by McAuliffe and Ward, 2006; and similar mismatches between EPG patterns and the perception of /Σ/ reported by Timmins et al (2009) for speakers with Down syndrome). McAuliffe, Ward, and Murdoch (2006) report the opposite effect for speakers with Parkinson disease, wherein apparently “normal” EPG patterns for lingual consonants are associated with consonants perceived as “imprecise”.…”
Section: 0 Candidate Measures For the Evaluation Of Dbs Effects On mentioning
confidence: 99%
“…EPG has been used to study lingual consonant production in speakers with dysarthria, including speakers with PD (see, for example, McAuliffe, Ward, & Murdoch, 2006 a, b; Kuruvilla, Murdoch, & Goozée, 2009; Timmins et al, 2009; and review in McAuliffe & Ward, 2006). As reviewed by McAuliffe and Ward (2006), several of these studies show differences in EPG patterns between speakers with dysarthria and neurologically-normal speakers, but the differences are often difficult (if not impossible) to interpret.…”
Section: 0 Candidate Measures For the Evaluation Of Dbs Effects On mentioning
confidence: 99%
“…Our results are in line with findings from some other earlier studies. Timmins, Cleland, Wood, Hardcastle, and Wishart (2009), for example, investigated the production of /∫/ in young people with Down’s syndrome. They show that many of those speakers, who differ from typically developing children in their palate shape, managed to produce perceptually acceptable productions of the fricative even if the articulation differed as compared to that of typically developing children and adults.…”
Section: Discussionmentioning
confidence: 99%
“…Hamilton (1993) noted increased tongue-palate contact for children with DS. Timmins et al (2007Timmins et al ( , 2009 found increased articulatory variability in fricative production of young people with DS when compared with a typically developing (TD) group matched for cognitive age. These detailed studies help to provide more answers regarding the specific speech errors displayed in children with DS.…”
Section: Introductionmentioning
confidence: 97%
“…However, most of these studies look at phonological processes (Stoel-Gammon, 1980;Smith and Stoel-Gammon, 1983;Bleile and Schwarz, 1984;Crosley and Dowling, 1989) and lack detailed phonetic analyses. A few studies have provided more detailed phonetic analyses of speech in DS using instrumental techniques such as acoustic analysis and electropalatography (EPG) (Hamilton, 1993;Brown-Sweeney and Smith, 1996;Callahan Mandaluk, Zajac, Harris, Roberts, and Cox, 2006;Timmins, Hardcastle, Wood, McCann, and Wishart, 2007;Timmins, Cleland, Wood, Hardcastle, and Wishart, 2009). Hamilton (1993) noted increased tongue-palate contact for children with DS.…”
Section: Introductionmentioning
confidence: 98%